Meta-analysis: adherence to colorectal cancer screening and the detection rate for advanced neoplasia, according to the type of screening test - Hassan, C.; Rossi, P. Giorgi; Camilloni, L.; Rex, D. K.; Jimenez-Cendales, B.; Ferroni, E.; Borgia, P.; Zullo, A.; Guasticchi, G.; Group, HTA (Alimentary pharmacology & therapeutics, 2012)
Summary Background A variety of tests have been proposed for colorectal cancer (CRC), giving rise to uncertainty regarding the optimal approach. The efficacy and effectiveness of different tests are related to both screenee participation and the detection rate. Aim To perform a meta‐analysis on adherence and detection rates of CRC screening tests. Methods Relevant publications were identified by MEDLINE/EMBASE and other databases for the period 1999–2012. A previous systematic review was used for the period before 1966–1999. RCTs and controlled studies including a direct comparison of the uptake rates among different options for CRC screening were included. Adherence and detection rates for advanced neoplasia and cancer were extracted. Risk for bias was ascertained according to CONSORT guidelines. Forrest plots were produced based on random‐effect models. Results Fourteen studies provided data on 197 910 subjects. Endoscopic strategies were associated with a lower participation (RR: 0.67, 95% CI: 0.56, 0.80) rate, but a higher detection rate of advanced neoplasia (RR: 3.21, 95% CI: 2.38, 4.32) compared with faecal tests. FIT was superior to g‐FOBT with regard to both adherence (RR: 1.16, 95% CI 1.03, 1.30) and detection of advanced neoplasia (RR: 2.28, 95% CI 1.68, 3.10) and cancer (RR: 1.96, 95% CI: 1.2, 3.2). Conclusion The superior accuracy of endoscopy compared with faecal tests minimised any impact of the participation rate in determining the detection rate of advanced neoplasia in a screening setting.